2002
DOI: 10.1115/1.1507769
|View full text |Cite
|
Sign up to set email alerts
|

Axial Loading of Bonded Rubber Blocks

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Note that a much flatter bulging profile was observed in Mott and Roland's compression experiments (Mott and Roland, 1995) on bonded slender rubber cylinders ( 0:22 < a=h < 0:54). Later on, without pre-assuming the lateral bulging shape, Horton, Tupholme and Gover obtained nonparabolic bulging profiles (Horton et al, 2002;Horton et al, 2003) for bonded rubber blocks under axially loading, which qualitatively captured this flatter profile for small aspect ratio in Mott and Roland's experiments (Mott and Roland, 1995) and can decay to parabola-like shape when the aspect ratio is large (e.g. a=h > 1).…”
Section: Numerical Resultsmentioning
confidence: 92%
“…Note that a much flatter bulging profile was observed in Mott and Roland's compression experiments (Mott and Roland, 1995) on bonded slender rubber cylinders ( 0:22 < a=h < 0:54). Later on, without pre-assuming the lateral bulging shape, Horton, Tupholme and Gover obtained nonparabolic bulging profiles (Horton et al, 2002;Horton et al, 2003) for bonded rubber blocks under axially loading, which qualitatively captured this flatter profile for small aspect ratio in Mott and Roland's experiments (Mott and Roland, 1995) and can decay to parabola-like shape when the aspect ratio is large (e.g. a=h > 1).…”
Section: Numerical Resultsmentioning
confidence: 92%
“…They presented approximate expressions to E a for blocks of circular and long rectangular cross-section, which were derived not only with the reasonable assumption that plane cross-sections of the block normal to the axis of the block remain plane but also with the free lateral surfaces assumed to have parabolic deformed shapes. On the other hand, the analyses of Horton et al (2002Horton et al ( , 2003 were completed without the necessity of making this second assumption, and in fact they confirmed the invalidity of assuming a parabolic lateral profile especially for blocks whose shape factor is small. Subsequently, Gent and Meinecke (1970) suggested that the apparent Young's modulus, E GM a , for a block of elliptical cross-section, with semi-major and minor axes a and b, and of axial height h, could be determined from…”
Section: Introductionmentioning
confidence: 90%
“…The analytical techniques used are generalizations of those developed by Horton et al (2002Horton et al ( , 2003 in studying blocks of circular and annular cross-sections. Gent and Lindley (1959) and Gent (1994) developed widely used approximate relations for the apparent Young's modulus, E a , for bonded blocks of incompressible rubber subjected to compression.…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed in Pinarbasi et al (2006) in detail, in the last century, many researchers (e.g., Lindley, 1979;Gent, 1994;Horton et al, 2002) have studied the behavior of rigidly-bonded elastic layers. Most of these studies have been conducted to determine their compression stiffness.…”
Section: Introductionmentioning
confidence: 99%